2021
DOI: 10.1088/1755-1315/807/4/042055
|View full text |Cite
|
Sign up to set email alerts
|

Growth and production of paddy rice (Oryza sativa L.) in various planting systems and types of liquid organic fertilizers

Abstract: This study aims to determine the growth and production of rice in various planting systems and types of liquid organic fertilizer. The research was conducted in Rijang Panua Village, Kulo District, Sidenreng Rappang Regency from May to August 2016. The research was conducted based on a split plot design with main plot set was planting system consisted of three levels, namely: the tile planting system (20 cm × 20 cm), the legowo planting system 4:1 (40 cm × 20 cm × 20 cm), and 2:1 legowo planting system (40 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Puteri et al (2021) reported that plant height, number of leaves, stem diameter, ear weight, and ear length of sweet corn were not affected by Tithonia (Tithonia diversifolia) LOF. Combining the planting system and the Gliricidia leaves + banana weevil LOF resulted in higher rice yields than Gliricidia tree leaves or banana weevils LOF (Mollah et al, 2021). Plant height, number of leaves, and flowering time were higher in the 15 ml L -1 liquid fertilizer treatment than in the 20 ml L -1 LOF or control treatments (Ridwan et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Puteri et al (2021) reported that plant height, number of leaves, stem diameter, ear weight, and ear length of sweet corn were not affected by Tithonia (Tithonia diversifolia) LOF. Combining the planting system and the Gliricidia leaves + banana weevil LOF resulted in higher rice yields than Gliricidia tree leaves or banana weevils LOF (Mollah et al, 2021). Plant height, number of leaves, and flowering time were higher in the 15 ml L -1 liquid fertilizer treatment than in the 20 ml L -1 LOF or control treatments (Ridwan et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…The use of LOF also boosted rice production. A 2:1 legowo planting system and a liquid organic fertilizer made from Gliricidia leaves + banana weevil produced the highest yields per hectare (Mollah et al, 2021).…”
Section: Soybeansmentioning
confidence: 99%
“…Research by [16] shows that the use of organic materials can significantly increase rice yield (16%). A study by [17] indicates that the use of organic fertilizer significantly affects the number of productive tillers and the number of leaves per rice plant.…”
Section: Adapting Planting Patterns To Increase Rice Pi 400 In Irriga...mentioning
confidence: 99%